EVALUASI PENGELOLAAN ASET TETAP KANTOR SEKRETARIAT DAERAH KOTA PONTIANAK BERDASARKAN PSAP NO. 07 DAN PERATURAN MENTERI DALAM NEGERI NO.19 TAHUN 2016 - Kurniawan, Indra B1031141024 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
An agency certainly can not be separated from fixed assets in carrying out its operational activities, fixed assets have a permanent property that indicates where the relevant asset can be used in the long term (more than one accounting period). Fixed assets are reported on the balance sheet in the sequence of their longest useful lives, starting from land, building and so on. The purpose of this research is to know the Evaluation of the management of fixed assets referring to Government Accounting Standard No. 07 and Regulation of the Minister of Home Affairs No. 19 to the Regional Secretariat of Pontianak City.The research method used by writer is descriptive qualitative analysis. By means of analysis in the form of literature study, interview, document review, and straight line method in calculating the depreciation. The source of this research is the Regional Secretariat of Pontianak City.The results of this study are the management of fixed assets implemented by the Regional Secretariat of Pontianak City has been maximally implemented but there are still some steps that are not in accordance with the system and procedures of the cycle of management of local property as stipulated in the Minister of Home Affairs Regulation No.19 of 2016 on guidelines for the management of regional properties. Straight line method as depreciation measurement is in accordance with depreciation method for application in depreciation policy of fixed assets in the form of one of the building belonging to the Regional Secretariat of Pontianak City.Â Keywords: Evaluation, Management of Fixed Assets, Regulation of the Minister of Home Affairs No.19 of 2016, PSAP No. 7